2019
DOI: 10.15376/biores.14.2.3432-3444
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic properties of Norway spruce wood modified with staining fungus (Sydowia polyspora)

Abstract: Effects of biological modification of Norway spruce wood with the wood-staining fungus Sydowia polyspora were evaluated relative to select physical and acoustical characteristics (PACHs), including the density (ρ), dynamic modulus of elasticity along the wood grain (EL), specific modulus (Esp), speed of sound along the wood grain (cL), resonant frequency (fr), acoustic constant (A), logarithmic decrement (ϑ), loss coefficient (η), acoustic conversion efficiency (ACE), sound quality factor (Q), and sound timbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 23 publications
(27 reference statements)
1
4
0
6
Order By: Relevance
“…From a qualitative point of view, it can be concluded that the UV and thermal treatment led to an improvement in the acoustic and elastic parameters of the wood selected for musical instruments, as characterized by the relatively low thickness (maximum 4 mm) studied in this paper. In agreement with the above findings, the literature data [17,24,25,28,[48][49][50][51][52][53] confirm that the ultrasound velocity and dynamic elastic modulus of the aged wood shift to higher values when compared to that of recently produced wood.…”
Section: Changes In Acoustic Propertiessupporting
confidence: 86%
“…From a qualitative point of view, it can be concluded that the UV and thermal treatment led to an improvement in the acoustic and elastic parameters of the wood selected for musical instruments, as characterized by the relatively low thickness (maximum 4 mm) studied in this paper. In agreement with the above findings, the literature data [17,24,25,28,[48][49][50][51][52][53] confirm that the ultrasound velocity and dynamic elastic modulus of the aged wood shift to higher values when compared to that of recently produced wood.…”
Section: Changes In Acoustic Propertiessupporting
confidence: 86%
“…To do so, various modification techniques are available. According to the types of properties required for the finished wood product, the natural wood scaffold will undergo a modification triggered by mechanical, [20] thermal, [21] chemical, [22] or biological [23] methods (or a combination of those). The goal of these modifications is always to alter the structure and/or the composition of wood, to obtain enhanced performances or new characteristics for novel applications.…”
Section: Sustainable Approaches Towards Wood-based Materialsmentioning
confidence: 99%
“…O tratamento térmico é realizado quando se deseja alterar a estrutura física e química da madeira com a intenção de provocar degradação ou rearranjo dos seus principais constituintes, modificando dessa forma algumas de suas propriedades físicas e mecânicas. Da mesma forma, modificações da madeira utilizando processos de acetilação; tratamentos com melamina e fenol formaldeído [1,2]; e modificação biológica com fungos que mancham ou destroem a madeira [1,3] podem ser usados para modificar as propriedades relevantes.…”
Section: Introductionunclassified